Stent overlapping and geometric curvature influence the structural integrity and surface characteristics of coronary stents - Anderson, Peter G.; Halwani, Dina O.; Brott, Brigitta C.; Lemons, Jack E.; Anayiotos, Andreas; Kapnisis, Konstantinos (My University, 2012)
A common clinical practice in interventional procedures, is the deployment of two or more overlapping stents, especially in areas of branches and bifurcations where the stenotic area is diffuse and cannot be covered by a single stent or in the cases of treating long or recurrent lesions. However, complex in vivo conditions such as vessel tortuousity, high curvature, vascular wall stresses as well as blood flow wall shear stresses and diffuse calcification, may cause additional interactions within overlapping stents resulting in enhanced surface damage and fracture of stents. Preliminary studies have revealed that some stents undergo corrosion and fatigue-induced fracture in vivo, with significant release of metallic ions into surrounding tissues. A direct link between corrosion and in-stent restenosis has not been clearly established; nonetheless in vitro studies have shown that relatively high concentrations of heavy metal ions can stimulate both inflammatory and fibrotic reactions, which are the main steps in the process of restenosis. This study presents the outcome of in vitro accelerated biomechanical testing of Nitinol stents placed in mock arteries in single and overlapping configurations with various degrees of curvature. The effect of overlapping dissimilar materials was also investigated by testing multiple alloy stent combinations combining NiTi with CoCr or SS stents.
Keywords: Stents; Corrosion; In-stent restenosis; Nitinol stents